Заклади охорони здоров’я як спеціальні суб’єкти медичних правовідносин в умовах подальшого реформування системи охорони здоров’я в Україні - Кройтор, В. А.; Kroitor, V. A. (Науковий вісник Міжнародного гуманітарного університету. Сер.: Юриспруденція. - 2023. - № 65. - С. 38-42, 2023)
Виявлено юридичні ознаки закладу охорони здоров’я як спеціального суб’єкта медичних правовідносин. Розкрито правовий статус закладу охорони здоров’я. Виокремлено особливості кластерної системи охорони здоров’я, визначено загальні та спеціальні юридичні ознаки закладу охорони здоров’я, сформовано рекомендації щодо подальших наукових розвідок.

The article defines the characteristics of a healthcare institution as a special subject of medical legal relations. The distinction of legal characteristics of a healthcare institution as a legal entity is urgent, considering the implementation of healthcare reform, gradual updating of medical legislation, and the need for post-war reconstruction of the medical field. It is emphasized that a healthcare institution has both general legal characteristics of a legal entity and special features determined by its field of activity. Healthcare institutions can be divided into private and public law legal entities (state, municipal institutions created by administrative order). The analysis of medical legislation highlights the appropriateness of distinguishing between business entities that practice medicine and healthcare institutions (as general and special). It is determined that a healthcare institution is a unique economic subject, as its activity has social value and should be in demand by the population. Attention is drawn to the fact that the social component of a healthcare institution manifests in its comprehensive nature – socio-economic. Meanwhile, a healthcare institution has an element of risk in its activity. To operate, a healthcare institution must have specific documentary support, especially a charter, a license, documents regarding the provision of medical practice. It is established that the formal procedure for creating a healthcare institution includes the following elements: decision-making about its formation; state registration; obtaining a license for medical practice; registration in the Registry of Economic Entities in the Healthcare Sector. It is emphasized that the economic activity of a healthcare institution has a special purpose – medical services to the population. This activity in the process of implementation should have certain monitoring regarding the provision of patient rights to receive quality medical care. It is established that in the current conditions of healthcare system reform, there is a transition to a cluster system, which requires certain improvements, in particular, the need to combine actual medical practice and medical innovations, and to introduce new forms of public-private partnership.

Выявлены юридические признаки учреждения здравоохранения как специального субъекта медицинского правоотношения. Раскрыт правовой статус учреждения здравоохранения. Выделены особенности кластерной системы здравоохранения, определены общие и специальные юридические признаки учреждения здравоохранения, сформированы рекомендации по дальнейшим научным исследованиям.
Health care institutions as special subjects of medical legal relations in the conditions of further reform of the health care system in Ukraine
Keywords: заклад охорони здоров’я; health care institution; заведение здравоохранения; медичні правовідносини; medical legal relations; медицинские правоотношения; юридична особа; legal entity; юридическое лицо; ознаки юридичної особи; signs of legal persons; признаки юридического лица; кластер; cluster; медичні послуги; medical services; медицинские услуги; господарська діяльність; economic activity; хозяйственная деятельность